Suboptimal Micronutrient Intake among Children in Europe - Boris Kaganov (Nutrients, 2015)
Adequate dietary intake of micronutrients is not necessarily achieved even in resource-rich areas of the world wherein overeating is a public health concern. In Europe, population-based data suggests substantial variability in micronutrient intake among children. Two independent surveys of micronutrient consumption among European children were evaluated. Stratified by age, the data regarding micronutrient intake were evaluated in the context of daily requirements, which are typically estimated in the absence of reliable absolute values derived from prospective studies. The proportion of children living in Europe whose intake of at least some vitamins and trace elements are at or below the estimated average requirements is substantial. The most common deficiencies across age groups included vitamin D, vitamin E, and iodine. Specific deficiencies were not uniform across countries or by age or gender.  Micronutrient intake appears to be more strongly influenced by factors other than access to food. Substantial portions of European children may be at risk of reversible health risks from inadequate intake of micronutrients. Despite the growing health threat posed by excess intake of calories, adequate exposure to vitamins, trace elements, and other micronutrients may deserve attention in public health initiatives to optimize growth and development in the European pediatric population.